Atelier sur L'Acceleration de la Reutilisation dex Eaux Usees au Maroc: Analyse Couts-Avantage et Possibilites D'Investissment - Brouziyne, Youssef (2023)
This consultation workshop was organized by IWMI through its Regional Office for the Middle East and North Africa in Cairo, jointly with ANAFIDE, the Moroccan National Committee for International Commission on Irrigation and Drainage (ICID), and was held on December 20 and 21, 2022 at the FAIRMONT Rabat-Salé hotel. The ultimate objective of this workshop was to contribute to the development of the water reuse sector in Morocco through the initiation of a dialogue around investment options and the different financing possibilities for the treatment and water reuse for various agricultural activities and other purposes; as well as exploring various cost-benefit analysis approaches for an optimal set-up of treatment and sustainable reuse projects. The workshop falls within the framework of the CGIAR’s Regional Integrated Initiative F2R-CWANA WP 4, which is led by IWMI and works for better productivity and more sustainable integration between the Water, Agriculture, Energy and Territory systems.